PELAKSANAAN PENANGGULANGAN KEMISKINAN STUDI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI - Torrido, Aryan (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
To reduce poverty rates in Indonesia, the government has introduced a program called PNPM Mandiri since 2007. The program aims to improve the quality of life and employment opportunities for the poor that is based on self-empowerment. The program is expected to be an effective tool to address poverty as is done by and for the community itself. Cooperation between the parties involved (the public, local governments and other interested parties) is critical to its success. As a priority, PNPM Mandiri is being focused on the provision and improvement of social and economic facilities, the provision of micro-loans to start economic activities for the poor, and to improve the ability of the public and local governments with training in business skills, organizational and financial management, as well as the implementation of governance good. So far there are some difficulties encountered during the implementation of programs.